The Effects of the SQ4R in Developing Grade 6 Students’ Pronunciation of Consonant Clusters - Wachirawit Charoenchai,; Autthapon Intasena,; Thussaneewan Srimunta,; Suarsaraha Suwannathep, (Journal of Educational Issues, 2024)
The ability to pronounce consonant clusters is essential for the communicative processes of a language. The SQ4R teaching model, normally employed in reading comprehension development studies, could be adapted to benefit a speaking classroom. The purposes of the study were 1) to investigate the effects of the SQ4R technique on Thai students’ consonant cluster pronunciation and 2) to study student satisfaction with the SQ4R technique in developing consonant cluster pronunciation. The participants were 40 grade 6 students in a public school in Thailand. The participants were chosen using the purposive sampling method. The criteria emphasize the heterogeneous characteristics of first language, experiences in foreign countries, and dialects. The instruments were 1) a learning management plan designed using the activities of the SQ4R technique in developing the pronunciation of consonant clusters, 2) consonant clusters pronunciation assessment form, and 3) a satisfaction questionnaire. The data were analyzed using percentages, mean scores, standard deviation, and an effective index with the determining criteria of 75/75. The results of the study indicate the benefits of the SQ4R technique to both in-process and end-product outcomes. Moreover, it was also found that the participants were satisfied with the processes provided by the learning management. The results of the study provide academic implications for further research and pedagogical implication for educational personnel seeking to solve problems in developing students’ pronunciation.